PUBLIK FIGUR DALAM IKLAN TESTIMONIAL - Duto Hartanto, Deddi (Institute of Research and Community Outreach - Petra Christian University, 2000)
Testimonial advertising seemingly identical with famous figure such as artist%2C sportmen or others. They are all branded as